FACTORS THAT AFFECT STUDENT SATISFACTION WITH STEBI TANGGAMUS SERVICES - Agustiyani, Vina Putri (Institut Bakti Nusantara, 2024)
This study aims to analyze the factors that affect student satisfaction with STEBI Tanggamus services, including the quality of academic services, the quality of administrative services, the availability of learning facilities, and the ease of access to information. The research method used was quantitative with a survey approach, involving 150 active student respondents who were selected using the proportional random sampling technique. Data were collected through questionnaires and analyzed using multiple linear regression. The results of the study show that the four independent variables have a positive and significant effect on student satisfaction, both partially and simultaneously. The quality of academic services is the dominant factor that affects student satisfaction, followed by ease of access to information, the quality of administrative services, and the availability of learning facilities. The value of the determination coefficient (R²) of 0.568 showed that 56.8% of the variation in student satisfaction could be explained by the variables studied, while the rest were influenced by other factors outside the study. These findings indicate that improving student satisfaction requires comprehensive improvements in academic, administrative, facilities, and information systems.